The National Research Council and Seventy-five Years of Agricultural Research in Canada - Estey, Ralph (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1991)
AbstractVarious aspects of the agricultural research that has been supported or carried out by the National Research Council of Canada during its first 75 years are reviewed. This research has ranged from such practical problems as: how to improve the edibility of oils from oilseed crops; how to improve the keeping quality of farm produce in storage; and how to control diseases and pests of farm animals and plants, to genetic engineering; the creation of new trans-genic plants and custom-designed enzymes for the benefit of agriculture.